Tata Laksana Hipoglikemia pada Pasien Diabetes: Tinjauan Pustaka - Ricky Pramudya; Siti Haura Amiralevi (PT Kalbe Farma Tbk., 2025)
Hypoglycemia is a complication of diabetes mellitus (DM) that may be deleterious. The most frequent cause of hypoglycemia in diabetes patients is inappropriate doses of insulin and/or anti-diabetic drugs. Hypoglycemia occurs more often in type 1 DM patients than in type 2 DM patients. Prompt recognition and treatment is critical because hypoglycemia increased morbidity and mortality.